WTO Agreement on Agriculture the Implementation Experience : Developing Country Case Studies (Food and Agriculture Organization of The United Nations (FAO), 2003)
In 1999, FAO initiated a major exercise to evaluate the impact of the agreement on Agriculture (AoA) on Agricultural trade and food security in developing countries fourteen country case studies were commissioned and an overview paper synthesizing these experience.